Exploration and practice on integration of ideological, political courses into professional courses of cyberspace security specialty - Guyue LI; Aiqun HU (网络与信息安全学报)
Considering the requirements of cyberspace security talents training, this paper explored the direction and emphases of ideological and political education with the course of “new progress in cyberspace security” as an example.Ideological and political goals, elements and resources were analyzed and a “point-line-plane” scalable practical method was formed.The effectiveness of course ideological was evaluated from multiple dimensions, including the degree of integration, students’ satisfaction and sustainability.The practice results showed that teaching team and students have deeper understanding of the necessity and importance of course ideological.When students are learning these sophisticated technologies, they are also inspired by the spirit of patriotism, dedication and strive to make progress, which strengthens their determination to devote to the national cyberspace security.This course will continue integrating ideological, political courses into professional courses, optimizing the political target and teaching methods.It adapts to the demands of reformation and development in higher education and provides a useful reference for related courses in cyberspace security specialty.